2012
DOI: 10.1007/s00248-012-0106-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Salmonella Population Dynamics in Water and Biofilms

Abstract: Members of the bacterial genus Salmonella are recognized worldwide as major zoonotic pathogens often found to persist in non-enteric environments including heterogeneous aquatic biofilms. In this study, Salmonella isolates that had been detected repeatedly over time in aquatic biofilms at different sites in Spring Lake, San Marcos, Texas, were identified as serovars Give, Thompson, Newport and -:z10:z39. Pathogenicity results from feeding studies with the nematode Caenorhabditis elegans as host confirmed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…EHEC E. coli was also identified from different sources in Isamailia, Egypt (Selim et al, 2013 (Sha et al, 2013). Caenorhabditis elegans was fed with Salmonella and a control (E. coli).…”
Section: Nucleic Acids-based Detection Methodsmentioning
confidence: 99%
“…EHEC E. coli was also identified from different sources in Isamailia, Egypt (Selim et al, 2013 (Sha et al, 2013). Caenorhabditis elegans was fed with Salmonella and a control (E. coli).…”
Section: Nucleic Acids-based Detection Methodsmentioning
confidence: 99%
“…Some aquatic E. coli isolates showed close relationships with strains from human and bovine origins, suggesting that environmental isolates were originally derived from these sources. Sha et al (2013) demonstrated that pathogenic salmonellae could persist over time and stay viable in aquatic biofilms in high numbers. Walczak et al (2013) found that Legionella pneumophila can be found in lakes serving as a natural cooling system of a power plant, since thermally altered aquatic environments provide perfect conditions for the growth of L. pneumophila.…”
Section: Water and Waste Water Treatmentmentioning
confidence: 99%
“…Although the mammalian intestine tract is considered its natural habitat (3), Salmonella is constantly being shed into aquatic environments through human and animal feces (4). This pathogen has been detected in a wide range of natural settings, such as water (rivers, lakes, coastal waters, and sewage effluents) (4, 5), soil, and sediments, where it can survive for long periods (6, 7). The wide diversity of Salmonella serotypes and its survival capacity outside a definitive host contribute to its constant presence in aquatic environments (4).…”
Section: Genome Announcementmentioning
confidence: 99%